Dye-Doped Fe3O4 Nanoparticles for Magnetically Controlling Random Laser Parameters at Visible Wavelengths: Literature Review and Experiment - M. S. Al-Samak; J. M. Jassim (Indonesian Journal of Science and Technology, 2022)
The development of light-controlled electronic devices requires new possibilities of optical control via tuning of laser input parameters. Here, Fe3O4 superparamagnetic nanoparticles (SNPs) were doped with dye, and the controllability of parameters of a random laser, including the wavelength, threshold energy, and intensity under the absence and presence of an external magnetic field was studied. The prepared dye laser (Rh-640) showed strong magnetic controllability and switch ability under different pumping energies (1‒7 mJ), as well as good responsivity and durability at visible wavelengths. The applied magnetic field was utilized to modify the distribution of Fe3O4 SNPs with different concentrations and scattering behavior, altering the generation of coherent loops and laser action properties. Thus, it was possible to employ the magnetically controllable random laser in a variety of technological applications, including biology and optical communications